Early pregnancy diagnosis on large dairy farms and its role in improving profitability: Literature review - Fodor, István; Ózsvári, László (Animal welfare, Ethology and Housing Systems (AWETH), 2018)
The authors reviewed the factors related to the accuracy of the early pregnancy diagnosis methods used on dairy farms, and summarized the results of the studies on the production and economic consequences of early pregnancy diagnosis. Transrectal ultrasonography and pregnancy-associated glycoprotein tests allow for accurate diagnosis about one week earlier than rectal palpation. Therefore, the breeding interval can be shortened and days open can be reduced. However, a drawback of the early diagnosis is that a larger proportion of the naturally occurring pregnancy losses is observed. Since iatrogenic pregnancy loss is more costly than the increase in the number of open days, it is important to use a diagnostic method with high sensitivity and negative predictive value. The economic advantage of early pregnancy diagnosis is higher in herds with poor reproductive performance. Higher cost per day open and larger herd size result in shorter payback time of the investments in early pregnancy diagnosis methods.
Keywords: pregnancy diagnosis; dairy cattle; economics